Defining a clinically meaningful within-patient change threshold for the Cohen-Mansfield Agitation Inventory in Alzheimer’s dementia - Meunier, Juliette; Creel, Kristin; Loubert, Angély; Larsen, Klaus Groes; Aggarwal, Jyoti; Hefting, Nanco; Oberdhan, Dorothee (Frontiers in Neurology, 2024)
Introduction: The Cohen-Mansfield Agitation Inventory (CMAI) quantifies the frequency of agitation behaviors in elderly persons. This post hoc analysis of data from the brexpiprazole clinical program aimed to determine a meaningful within-patient change (MWPC) threshold for CMAI Total score among patients with agitation associated with dementia due to Alzheimer’s disease. Methods: Data were included from three 12-week, multicenter, randomized, double-blind, placebo-controlled, parallel-arm trials of brexpiprazole for the treatment of agitation associated with dementia due to Alzheimer’s disease (ClinicalTrials.gov identifiers: NCT01862640, NCT01922258, NCT03548584). Change in CMAI Total score (range 29–203; higher scores indicate higher frequency of agitation behaviors) from baseline to Week 12 was the primary endpoint in each trial. MWPC thresholds were estimated from anchor-based mean change analyses and receiver operating characteristic (ROC) curves. The Clinical Global Impression – Severity of illness (CGI-S) and Clinical Global Impression – Improvement (CGI-I) scales, both as related to agitation, were used as anchors. Empirical cumulative distribution functions (eCDFs) and probability density functions (PDFs) were plotted as supportive evidence. Distribution-based methods were also employed. Results: Data from 898 patients were analyzed (mean age, 73.7 years; mean baseline CMAI Total score, 73.8). The mean CMAI Total score change corresponding to a difference of small improvement vs. stable (CGI-S 1-point decrease vs. no change), or minimally improved vs. no change (CGI-I rating of 3 vs. 4), ranged from -10.6 to -13.5 points. The mean CMAI Total score change corresponding to a difference of moderate improvement vs. stable (CGI-S 2-point decrease vs. no change), or much improved vs. no change (CGI-I rating of 2 vs. 4), ranged from -20.2 to -25.7 points. ROC curve analyses generally produced smaller estimates of meaningful change. eCDFs and PDFs showed good distribution and separation of CMAI Total score change between CGI-S/CGI-I categories. In distribution-based analyses, the minimal detectable change for CMAI Total score (10.5–11.8 points) was generally lower than anchor-suggested thresholds. Conclusion: Triangulation of evidence from anchor- and distribution-based analyses supports an MWPC threshold for CMAI Total score of -20 points, with a threshold range of -15 to -25 points, in patients with agitation associated with dementia due to Alzheimer’s disease.